Pemberdayaan Kelompok PKK RW 1 Desa Ganggang melalui Produksi Eco-Antimosco Berbasis Daun Pepaya, Serai, dan Daun Salam: Pengabdian - Aulia Bayu; Sugiantoro, Sugiantoro; Setiawan, Heri Cahyo Bagus (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity aims to empower members of the PKK RW 01 in Ganggang Panjang Village, Tanggulangin District, Sidoarjo Regency, to utilize natural ingredients as environmentally friendly mosquito repellents. The program focuses on training in the production of Eco-Antimosco, a spray and aromatherapy candle product made from papaya leaves, lemongrass, and bay leaves. This activity was carried out in response to the high number of Dengue Fever (DHF) cases and the low utilization of local herbal ingredients as alternative solutions in the community. The implementation of the activity consists of three stages: preparation, implementation, and evaluation. The preparation stage includes preparing tools, materials, and product formulation trials to ensure stable results. Implementation stage includes the opening, presentation of materials, and demonstration of product production. The evaluation stage is carried out through observation and distribution of questionnaires to assess the increase in knowledge, skills, and attitudes of participants after the training. Results of the activity show an increase in participants' ability to understand the function of the materials, follow the production process correctly, and produce natural mosquito repellent products that are effective and safe for use in the household environment.